Geology of Bayat area and resistivity study of ground water potential in Gunung Kidul,Yogyakarta, Indonesia. - Aina Afiqah Suhaimi (2019)
Generally, the study area consists of two regencies that is Bayat and Gunung Kidul. The study area can be divided into three which are Jiwo hills, alluvial plains and Gunung Kidul (Southern Mountain). The Jiwo hills area located in the north part of the study area and alluvial plains that are located in the centre part of the study area have abundant groundwater resources as the area had undergone a series of intrusion which leads to the existence of complex geological structures. Alluviumis a good groundwater recharge hence, there are abundant of water wells in the villages that are located in these areas. On the other hand, the Gunung Kidul Regency (Southern Mountain) dominantly consists of steep slopes that hardens the process of groundwater exploration despite the lithology of the area that is dominated by sedimentary rocks which are also a good groundwater recharge. The purpose of this study is to update the geological map of the study area and also to investigate the groundwater potential in Gunung Kidul area using the vertical electrical sounding (VES) method which involves resistivity as the main parameter. In the Gunung Kidul area, three resistivity lines were conducted and based on the lithological factors, it can be interpreted that there is a good groundwater resource that could be useful for domestic uses for the locals. This groundwater exploration is necessary due to the lack of water wells and groundwater resource in the area.